Enhancing Learning Motivation and Student Engagement through Virtual Reality in Virus Topic Learning - Luther Jonathan Samori; Adisti Ratnapuri (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The integration of innovative technologies into biology education has become increasingly important for enhancing students' motivation and engagement, particularly when studying abstract topics such as viruses. This study aimed to examine students' responses to the use of Virtual Reality (VR) in learning about viruses in biology. The study employed a Classroom Action Research (CAR) design based on the model of Kemmis and McTaggart and was conducted in two cycles. Data were collected through student questionnaires. The results showed that the average response in the first cycle reached 68.73%, which was categorized as sufficient. In the second cycle, involving 35 students, the average percentage increased to 81.79%, indicating a higher level of positive responses. More than 80% of students reported increased motivation to learn and greater active participation in discussions, group work, and interactions with learning materials through VR simulations. These findings suggest that VR-supported learning can enhance students' motivation and engagement in understanding complex biological concepts.